Exploring English Literacy Learning at the First Grade of Elementary School - Razimona, Rizka; Silvhiany, Sary; Vianty, Machdalena (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
Teaching English to first-grade elementary school children presents its own challenges for teachers. This is because children at this age have characteristics such as having a short attention span, enjoying playing, and learning more effectively when they are having fun. On the other hand, children in this group are still learning to read and write in the national language. The purpose of this research is to explore how English literacy learning is implemented, to find out the inhibiting and encouraging factors in implementing English literacy learning in first-grade elementary schools, and to find out strategies that can be used to overcome the factors that hinder the implementation of English literacy learning in the classroom. one elementary school. The design of this research is descriptive qualitative. The data sources in this research are first-grade elementary school English teachers, school students, and learning documents. The data collection techniques used were observation, interviews, and documentation. Some of the results of this research are that teachers apply various methods in teaching, such as songs, drills, lectures, reading aloud, memorizing, and games. Among these learning strategies, songs are the most effective strategy for introducing English to children. The challenges faced are that children are very active, get bored quickly, and a small number of children do not read fluently. Factors that can support English literacy learning are adequate learning aids such as the use of pictures and parental involvement at home to repeat English lessons and practice them at home